Cancer Imaging: pH‐Activatable MnO‐Based Fluorescence and Magnetic Resonance Bimodal Nanoprobe for Cancer Imaging (Adv. Healthcare Mater. 6/2016). Issue 6 (March 2016) - Hsu, Benedict You Wei; Ng, Michael; Tan, Aaron; Connell, John; Roberts, Thomas; Lythgoe, Mark; Zhang, Yu; Wong, Siew Yee; Bhakoo, Kishore; Seifalian, Alexander M.; Li, Xu; Wang, John
Abstract : On page 721, X. Li, J. Wang, and co‐workers report on a MnO‐based fluorescence/MRI dual‐modality nanoprobe for cancer imaging. While the encapsulated MnO nanoparticles can quench the fluorophores effectively prior to cellular uptake, fluorescence activation is triggered upon dissolution of the MnO nanoparticles to release Mn 2+ ions in the acidic lysosomal compartment of the cancer cells.